Early failure of a highly cross-linked polyethylene inlay after total hip arthroplasty probably due to insufficient irradiation. (December 2022) - Wahl, Peter; Mossu-Haas, Christine; Dommann-Scherrer, Corina; Wei, Kongchang; Eschbach, Lukas; Gehr, Peter; Benninger, Emanuel
Highly cross-linked polyethylene (XLPE) is a major advance in total hip arthroplasty (THA), as it suffers from less wear and thus is associated with lower revision rates than standard ultra-high molecular weight polyethylene. Early failures are reported rarely, and associated with specific design or manufacturing issues. We report a case requiring early revision due to adverse reaction to polyethylene particles. Investigations identified insufficient irradiation as the most probable cause of failure. Here are reported the features of a clinical case with determination of the material properties of the retrieved XLPE liner and establishment of the appropriate calibration curves as reference. Periprosthetic joint infection could be ruled out with appropriate sampling as cause for the inflammatory periarticular tumour. Histology identified a massive macrophagic reaction to micrometric polyethylene particles. No component malposition was present, nor any third-body wear. The trans-vinylene index (TVI) indicated insufficient and potentially detrimental irradiation of the polyethylene, while gel content, crystallinity, melting temperature and oxidation index remained within expected ranges. Histologically proven failure of a XLPE THA liner was identifiable despite correct implantation of the components. The cause of failure most probably was an inadequate irradiation, as indicated by determination of the TVI. This case underscores the importance of histologic workup even in aseptic revisions, and of detailed analysis of retrievals. The calibration curves provided are essential for analysis of other retrievals. Graphical abstract